2010
DOI: 10.1246/cl.2010.950
|View full text |Cite
|
Sign up to set email alerts
|

Indigo Dye as a Positive-electrode Material for Rechargeable Lithium Batteries

Abstract: The performance of indigo carmine (5,5¤-indigodisulfonic acid sodium salt) as a positive-electrode material for rechargeable lithium batteries was investigated. The prepared electrode showed an initial discharge capacity of 110 mA h g ¹1, which corresponds to two-electron-redox behavior. Furthermore, the electrode was shown to have good cycle-life stability.Indigo has been used for dyeing and printing, and its dark blue color has fascinated people all over the world since ancient times. 15 In particular, indig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 15 publications
5
69
0
Order By: Relevance
“…[38] Anthraquinone-based salts seem to show better cycling stability than lithiated oxocarbon salts. [165] Considering the similar atomic weight of H and Li, direct lithiation of pyromellitic diimide is a good route to avoid theoretical capacity reduction. [163] In contrast, anthraquinone bearing two sulfonate groups (-SO 3 Na, [9][10][11][12][13][14] could simultaneously enhance the cycling performance and lithium storage voltage (≈2.4 V) via the electron-withdrawing groups of -SO 3 Na.…”
Section: Stability-orientedmentioning
confidence: 99%
“…[38] Anthraquinone-based salts seem to show better cycling stability than lithiated oxocarbon salts. [165] Considering the similar atomic weight of H and Li, direct lithiation of pyromellitic diimide is a good route to avoid theoretical capacity reduction. [163] In contrast, anthraquinone bearing two sulfonate groups (-SO 3 Na, [9][10][11][12][13][14] could simultaneously enhance the cycling performance and lithium storage voltage (≈2.4 V) via the electron-withdrawing groups of -SO 3 Na.…”
Section: Stability-orientedmentioning
confidence: 99%
“…2e4 Recently, indigos and functionalized indigos were applied for optoelectronic devices, such as field effect transistors, 5e7 solar cells, 8,9 sensors, 10,11 and electrodes for ion batteries. 12,13 In particular, Pitayatanakul et al, reported on the halogen or phenyl group functionalized indigos for organic semiconductors. In this series of compounds, the indigos showed a herring-bone like structure for the halogen substitution derivatives, whereas a brickwork arrangement of the crystal structure was observed in the case of phenyl-derivatives because of pep interactions arising from the functionalization substitution at 5-position.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of organic materials that contain no scarce metal resources and a sodium-based electrolyte solution will realize a totally “rare metal-free” battery; however, the behaviors of such organic materials as the active materials of sodium battery systems are less well-known except for a few preceding examples181920. Previously, we reported the battery performance of a series of redox active organic materials in lithium electrolyte systems21222324252627. In the present study, we prove that indigo carmine (IC, Fig.…”
mentioning
confidence: 99%